Perbandingan Pengaruh Pemberian Ekstrak Zingiber officinale dengan Insulin terhadap Berat Plasenta pada Rattus norvegicus Model Diabetes Mellitus Pragestasional - Sepfrita Katerine Aftabuddin (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2018)
Diabetes mellitus is a chronic disease that occurs in the community, with 1.9% prevalence of in the world is and the seventh leading cause of death in the world. It is estimated to increase up to 21.3 million by 2030 if the pattern of Diabetes management is not well developed. In 2007, the prevalence of Pregestational Diabetes Mellitus in Indonesia was 12% and had an impact on placental development that was important during pregnancy for fetal survival with placental weight as the indicator. Diabetes Mellitus pregestational therapy is insulin, however, it often causes complications. Oral hyperglycemic drugs with ginger dose extract of 500mg/kgBW significantly decreased serum glucose levels in diabetic-induced rats. Ginger extract is expected to decrease blood glucose levels so as to increase the weight of placenta. The purpose of this study was to determine the effect of insulin and ginger extract on the weight of placenta Rattus norvegicus model of diabetes mellitus. This research is an experimental research using post test only control group design. The population used in this study was pregnant Rattus norvegicus with simple random sampling. The independent variables are insulin and ginger extract and the dependent variable is the weight of placenta. Data analysis for placental weight using Kruskal Wallis was continued by Post Hoc Bonferroni test. Test results for placental weight p>α (0.63 > 0.05) mean that there is no difference in placental weight between negative control, positive control, and treatment group. The conclusion of this study is there is no significant difference between groups, however, based on mean data the weight of placenta Rattus norvegicus model of diabetes mellitus with insulin and ginger extract therapy are higher than the control group